Making sense of the changing face of Google's search engine results page: an advertiser's perspective. Issue 1 (6th December 2017) - Sharma, Divya; Gupta, Agam; Mateen, Arqum; Pratap, Sankalp
Abstract : Purpose: Google commands approximately 70 per cent of search market share worldwide, resulting in businesses investing heavily in search engine advertising on Google to target potential customers. Recently, Google changed the way in which content and ads were displayed on the search engine results page. This reshuffling of content and ads is expected to affect the advertisers who advertise on Google and/or use it to drive traffic to their websites. The purpose of this study is to analyze the impact of these changes on various stakeholders. Design/methodology/approach: Data have been collected from various sources on the internet including blogs and discussion forums. Netnography has been used as it allows a detailed evaluation of the consumers' needs, wants and choices in a virtual space. Findings: The average cost-per-click for ads on the top positions is expected to increase. Advertisers whose ads usually occupy the lower positions would be adversely affected. To counter this, more emphasis should be placed on ad extensions and on product listing ads. In addition, organizations would benefit from increased efforts on search engine optimization. Practical implications: A variety of coping strategies have been developed that can help marketers to successfully navigate through the change, including the use of ad extensions and the use of product listing ads. Originality/value: This practice-focused paper offers guidelines for digital marketers to use sponsored search more effectively as part of their arsenal in light of some important changes recently made by Google. The potential of netnography as a research methodology has also been expanded by using it in a novel setting and in drawing up actionable insights.